Reflexiones sobre gestión y derecho ambiental en el Perú. Introducción al Dossier - Ortíz Sánchez, Iván (Pontificia Universidad Católica del Perú, 2025)
This article offers a brief historical and regulatory review of environmental management and environmental law in Peru, presenting some reflections on the challenges and issues of sustainable development. It also introduces the articles published in issue No. 15 of the Revista Kawsaypacha: Sociedad y Medio Ambiente (Kawsaypacha Journal: Society and Environment), which has been divided into three sections featuring highly interesting contributions and research.

Este artículo realiza una breve revisión histórica-normativa sobre la gestión y el derecho ambiental peruano, planteando algunas reflexiones sobre los retos y desafíos del desarrollo sostenible. De otro lado, presenta los artículos del Dossier: Política y gestión ambiental, publicado en el número 15 de la Revista Kawsaypacha: Sociedad y Medio Ambiente, los que se han dividido en tres secciones, con muy interesantes aportes e investigaciones.
Reflections on Management and Environmental Law in Peru. Introduction to the Dossier
Keywords: Politics; Management; Environment; Law; Sustainable Development; Política; Gestión; Ambiente; Derecho; Desarrollo sostenible; https://purl.org/pe-repo/ocde/ford#2.07.01